2017
DOI: 10.1111/desc.12546
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal stream function in the young child: an fMRI investigation of visually guided action

Abstract: Visually guided action is a ubiquitous component of human behavior, but the neural substrates that support the development of this behavior are unknown. Here we take an initial step in documenting visual-motor system development in the young (4- to 7-year-old) child. Through functional MRI and by using a new technique to measure the mechanisms underlying real-time visually guided action in the MRI environment, we demonstrate that children rely primarily on the IPS and cerebellum for this complex behavior. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 67 publications
(118 reference statements)
1
13
0
Order By: Relevance
“…Furthermore, the associations were seen across the cohort and were not confined to children born preterm, with neonatal hypoglycaemia or low socioeconomic status. It has recently been reported that visually guided movements recruit dorsal stream areas in children 4–7 years of age, and thus the standardized tests of gross and fine motor function we used in this study were likely to involve dorsal stream processing [16]. Together, these results suggest that the development of dorsal stream functions relating to motion perception and motor function are linked early in life.…”
Section: Discussionsupporting
confidence: 50%
“…Furthermore, the associations were seen across the cohort and were not confined to children born preterm, with neonatal hypoglycaemia or low socioeconomic status. It has recently been reported that visually guided movements recruit dorsal stream areas in children 4–7 years of age, and thus the standardized tests of gross and fine motor function we used in this study were likely to involve dorsal stream processing [16]. Together, these results suggest that the development of dorsal stream functions relating to motion perception and motor function are linked early in life.…”
Section: Discussionsupporting
confidence: 50%
“…Particularly, visuomotor representations are essential for humans' ability to interact with their surroundings and accordingly, by the age of 18 months, toddlers can adjust their hand position based on the shape of the object and a corresponding slot (Street et al, 2011). Moreover, excluding some quantitative differences, the underlying neural network (i.e., the dorsal pathway) that supports visuomotor behaviors was found to be in place at the age of 4 years old (James & Kersey, 2017). Yet, despite this early sensitivity, the current findings suggest that visuomotor representations are not yet mature in six-year-old children (and also see Kuhtz-Buschbeck et al, 1999, 1998.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, visuomotor behaviors develop early in-life, and by the age of 12 months, infants can reach to objects quite accurately (Street, James, Jones, & Smith, 2011). Moreover, the underlying neural network that is engaged in adulthood in visuomotor control, has also been observed in 4 year-old children (James & Kersey, 2017). However, as in the case of perception, detailed investigations of grasping behavior in children reveal developmental differences between adults and school-age children (e.g., Kuhtz-Buschbeck, Boczek-Funcke, Illert, Joehnk, & Stolze, 1999;Kuhtz-Buschbeck, Stolze, Jöhnk, Boczek-Funcke, & Illert, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…To date, the developmental trajectory of shape representations in the dorsal pathway has been largely unexplored: Previous studies have documented adult-like responses in the dorsal pathway, but the responses were obtained in experiments that included a visuomotor task (James & Kersey, 2017) or pictures of tools (Kersey et al, 2015;Dekker et al, 2011) that convey clear visuomotor associations. Here, we provide novel evidence that, similar to the ventral pathway, dorsal shape-processing mechanisms are present in childhood (8-10 years old), although they are not yet fully adult-like.…”
Section: Discussionmentioning
confidence: 99%